Low Rates of Colonoscopy Follow-up After a Positive Fecal Immunochemical Test in a Medicaid Health Plan Delivered Mailed Colorectal Cancer Screening Program - Beverly B. Green; Laura-Mae Baldwin; Imara I. West; Malaika Schwartz; Gloria D. Coronado (SAGE Publishing, 2020)
Background Follow-up colonoscopy after a positive fecal immunochemical test (FIT) is necessary for colorectal cancer (CRC) screening to be effective. We report colonoscopy follow-up rates after a positive FIT overall and by population characteristics in the BeneFIT demonstration pilot, a Medicaid health insurance plan-delivered mailed FIT outreach program. Methods In 2016, 2 health insurance plans in Oregon and in Washington state mailed FIT kits to Medicaid patients who, based on claims data, were overdue for CRC screening. We report follow-up colonoscopy completion rates after positive FIT, and differences in completion rates by age, sex, race, ethnicity, preferred language, and number of primary care visits in the prior year. This research was human subjects approved with a waiver of consent for data collection. Results The FIT positivity rates in Health Plan Oregon and Health Plan Washington were 7.9% (39/488) and 14.6% (125/857), respectively. Colonoscopy completion rates within 12 months of the positive test were 35.9% (14/41) in Health Plan Oregon and 32.8% (41/125) in Health Plan Washington. Colonoscopy completion rates were higher among individuals who preferred a language other than English (Non-English speakers 70.0%, English speakers 31.3%, P  = .04). Conclusion In a health plan-delivered mailed FIT outreach program, follow-up colonoscopy rates after a positive test were low. Additional interventions are needed to assure colonoscopy after a positive FIT test and to reap the benefits of screening.